Reporting quality of sham needles used as controls in acupuncture trials: a methodological evaluation - Ye-Seul Lee; Song-Yi Kim; Mariah Kim; Minseo Kim; Jiyoon Won; Hyangsook Lee; Myeong Soo Lee; Younbyoung Chae (BMC, 2022)
Abstract Objective The description of controls is important in acupuncture clinical trials to interpret its effectiveness without fallacy. This paper aims to evaluate the reporting quality of acupuncture studies on the characteristics of sham needles. Study design and setting Using a checklist developed from previously published reporting guidelines, the distribution of reported items and changes of reporting rates over time were investigated. Two-way ANOVA and linear regression were conducted. Results Original articles of RCTs of any design involving sham needles as controls were eligible for assessment. 117 trials from three 2-year time periods between 2009 and 2018 were included. Seven items out of 25 were reported in more than 50% of the studies. While significant differences of reporting scores among categories were observed, there were no significant differences among time periods; no significant improvement was observed over time. Conclusions Low reporting qualities of sham needles used in acupuncture studies may influence how researchers understand the effectiveness of acupuncture. This study evaluated previous publications from 2009 to 2018 and found that reporting qualities on sham needles did not improve over time. Further studies are required to validate the items used in this study to endorse better reporting of controls in acupuncture trials.